There is no place like home!: how willing are young adults to move to find a job? - Weiß, Julia; Ferrante, Livio; Soler-Porta, Mariano (Sustainability, 2021)
The European Union (EU) has undergone significant economic crises in recent years. Therein, young people were amongst the hardest hit groups, with youth unemployment rising as high as 50% in some member states. Particularly high rates of youth unemployment were often observed in rural areas, where labour market supply in relation to demand were notably divergent. One of the core pillars of the EU’s agenda is to tackle the persistent problem of youth unemployment. Since the recent crisis, this has been via the “Youth on the Move” initiative, which involves the promotion of intra- and international mobility of young adults in order to gain access to job opportunities. However, what has received little attention so far is the question of what the general willingness of young adults to move is like, and to what extent this varies, for example, depending upon the area they live in. This paper therefore asks if rural youth differ from youth in urban areas in relation to their willingness to move for a job within their country or to another country. Moreover, what influences the general willingness to be mobile? Based on the Cultural Pathways to Economic Self-Sufficiency and Entrepreneurship (CUPESSE) Survey, which includes data on 18-35-year-olds in a sample of 11 European countries, it is shown that living in a rural area is strongly associated with the willingness to move. Furthermore, it shows that rural youth are more willing to move within the country but less willing to move to another country. Based on the presentation of the various factors, which promote or curb mobility readiness, the results make it clear that the success of EU initiatives depends on the preferences and willingness of the target group in question.